Innovative Approaches to Funding Tertiary Education for Sustainable Development in Nigeria - ABDULLAHI, Adamu Maidallah; SURAJO, Aminu (Ilorin Journal of Education, 2024)
In the 21st century, financing of tertiary education has become a critical factor in achieving sustainable development in Nigeria. The objective of this study is to provide actionable insights for policymakers, educators, and stakeholders seeking to advance sustainable development through innovative financing within the scope of tertiary education. The paper is designed as a conceptual study that explores innovative approaches to financing tertiary education in the 21st century in order to attain Sustainable Development Goal number 4; which is quality education. The conceptual study investigates the role of tertiary institutions in Nigeria, challenges and opportunities associated with current financial models and proposes new strategies that can ensure equitable access to higher education while fostering economic, social, and environmental sustainability in Nigeria. However, the implications of the findings of the study implied that Nigeria can diversify funding sources, enhance sustainability, and improve the quality and relevance of tertiary education by embracing innovative financial models such as public-private partnerships, social impact bonds, technology-enabled fundraising, and income-share agreements, among others to transform Nigeria's tertiary education landscape for quality and equitable access to education for overall development and prosperity.